Estrategia universitaria basada en habilidades - Ronald Miranda-Chavarría; Vanessa Valerio-Hernández (Universidad Nacional, Costa Rica, 2004)
Defining a global strategy that universities can use in order to fulfill their mission and their vision of the future constitutes a vital task for university authorities. A skill-based University Strategy model is introduced in this paper as a conceptual and methodological resource to be used in the analysis and definition of institutional strategies within a university. We hereby present the fundamentals of the project, describe its strategic scenarios, and explain the process of strategy creation. This is illustrated through the experience of the global process of planning that the Universidad Nacional, Costa Rica, has gone through.